Percepções e experiências de mulheres atuantes no campo da saúde sobre violência de gênero - Lima, Fernanda Felício de (Universidade Federal de São Carlos, 2020)
In all modern societies, to a lesser or greater degree, the influence of the patriarchal system pervades social organizations and gender relations which, as a consequence, are unequally established and contribute to the establishment of multiple forms of domination, control and violence of men towards women. The interface between health and gender violence is evidenced by the role of the health system and its professionals in assisting victims of violence, as well as by the sectorial strategies for confronting the culture of violence as a determinant of the health process-disease-intervention. The field of Health composed by a large contingent of professional caregivers women, is not immune from being a space of reproduction of these structural violence , nor does it place these women in an armored place of the violence that they themselves seek to face from professional resources. Thus, the present study aimed at mapping and analyzing the perceptions of women working in the field of Brazilian Collective Health on gender violence lived and expressed in their daily lives, through the cut-out of a broad study entitled "Women of Collective Health: a portrait of who builds the field", fruit of the intervention-struggle research movement of women active in the field of Collective Health that form the Collective Adelaides: Feminisms and Health. It is a quanti-qualitative study, intervention-type research, which starts from the mapping method and from the theoretical references of black feminist epistemologies. The results are presented through the typification of violence perceived by women and its interface with the process of health work and their daily lives, that point to the persistence and severity of the violence expressed in the daily lives of women active in the field of Collective Health and the possible contributions of the deepening and analysis of this scenario from the articulation of the concepts of intersectionality, place of speech and policy of empowerment, for gender studies and possibilities of coping with these violence.
Perceptions and experiences of women active in the health field on gender violence
Keywords: Violência de gênero; Feminismo; Interseccionalidade; Saúde coletiva; Cotidiano; Gender-based violence; Feminism; Intersectionality; Collective health; Everyday life; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA